KONSTITUSIONALITAS PRESIDEN DALAM MEMBENTUK PERATURAN PEMERINTAH PENGGANTI UNDANG- UNDANG - Arifuddin Arifuddin (VERITAS, 2016)
According to Article 22 Paragraph (1) of the 1945 Constitution stated that 'inHappenings crunch that forced the President has the right set of governmentregulations in lieu of law'. Therefore the president has the constitutional rights inaccordance with the legislation in force in the issuing of Government Regulation inLieu of Law (Perppu) Number 1 Year 2013 regarding the Second Amendment toLaw Number 24 Year 2003 regarding the Constitutional Court, however, in issueda decree quo should qualify crunch forcing matters, and at least a race on expertopinion that has been formulated as a picture crunch forcing matters, namely: thestate never considered previously and demanded an immediate action withoutwaiting for the consent of the advance; there is an urgent need for action orreasonable necessity; limited time available (limited time) or there is a timecrunch; no other alternative is available or based on logical reasoning (beyondreasonable doubt) Another alternative is not expected to be able to cope with thesituation, so that the regulation has the determination is the only way to remedy thesituation; can not be replaced by other measures; The measure is temporary; andwhen action is taken, the parliament can not be real and earnest. So if it ismaterially the president can not be issued a decree quo, because it is not in mattersof urgency into force as the force crunch criteria. Formulation matters of urgencywas an act of force to avoid the arbitrariness of the authorities and as aconsequence as a legal state.